ปัจจัยส่วนบุคคลที่มีความสัมพันธ์กับสถานภาพรอพินิจ ของนิสิตระดับปริญญาตรี มหาวิทยาลัยทักษิณ / Personal Factors Relating to the Academic Probation of Thaksin University’s Undergraduate Students - Warangkhana Riansut, วรางคณา เรียนสุทธิ์ / (Journal of Community Development Research (Humanities and Social Sciences); Vol 10 No 1 (2560): January-March 2017, 2017)
การวิจัยครั้งนี้มีวัตถุประสงค์เพื่อศึกษาความสัมพันธ์ระหว่างปัจจัยส่วนบุคคลที่มีต่อสถานภาพรอพินิจของนิสิตระดับปริญญาตรี มหาวิทยาลัยทักษิณ ตัวอย่างที่ใช้ในการวิจัย คือ นิสิตระดับปริญญาตรีของมหาวิทยาลัยทักษิณ ที่ลงทะเบียนในภาคเรียนที่ 1 ปีการศึกษา 2558 จำนวน 599 คน ได้มาโดยวิธีการเลือกตัวอย่างแบบแบ่งชั้นภูมิอย่างมีระบบวงกลม เครื่องมือที่ใช้ในการเก็บรวบรวมข้อมูล คือ แบบสอบถามเกี่ยวกับปัจจัยส่วนบุคคลและสถานภาพของนิสิต สถิติที่ใช้ในการวิเคราะห์ข้อมูล ได้แก่ ความถี่ ร้อยละ และการทดสอบไคกำลังสอง ผลการวิจัย พบว่า เพศ ชั้นปีการศึกษา คณะ วิธีการสอบเข้าศึกษา การมีโรคประจำตัว/ปัญหาชู้สาว/ยาเสพติด สถานภาพสมรสของบิดา มารดา ระดับการศึกษาของบิดา และรายได้เฉลี่ยต่อเดือนของครอบครัว มีความสัมพันธ์กับสถานภาพของนิสิต อย่างมีนัยสำคัญที่ระดับ .01 ขณะที่สายการเรียนในระดับมัธยมศึกษาตอนปลาย ระดับการศึกษาของมารดา และอาชีพของมารดา มีความสัมพันธ์กับสถานภาพของนิสิตอย่างมีนัยสำคัญที่ระดับ .05      This research aimed to study the correlation among the personal factors which affect on the academic probation of Thaksin University’s undergraduate students. Samples used to study were 599 undergraduate students of Thaksin University who enrolled in the first semester of academic year 2015 which obtained by circular stratified systematic sampling method. The tool used to collect the data was a questionnaire about personal factors and undergraduate student’s status. The statistics used in data analysis were frequency, percentage, and Chi-square test. Research findings indicated that, sex, year of study, faculty, admission procedures, the diseases/problems of sexual/drug, marital status of parents, educational level of father, and average monthly income of family correlated with the undergraduate student’s status at the significance level .01. The major in high school, educational level of mother, and occupation of mother correlated with the undergraduate student’s status at the significance level .05
Keywords: ปัจจัยส่วนบุคคล ความสัมพันธ์ สถานภาพของนิสิต นิสิตปริญญาตรี; Personal Factor, Correlation, Undergraduate Student’s Status, Undergraduate Student